2018
DOI: 10.3390/ijms19051509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Aspects of Vitiligo Treatments

Abstract: Vitiligo is an asymptomatic but cosmetically disfiguring disorder that results in the formation of depigmented patches on skin and/or mucosae. Vitiligo can be segmental or non-segmental depending upon the morphology of the clinical involvement. It can also be classified as progressing or stable based on the activity of the disease. Further, the extent of involvement can be limited (localized disease) or extensive (generalized disease). The treatment of vitiligo therefore depends on the clinical classification/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 90 publications
1
58
0
7
Order By: Relevance
“…Patients who have vitiligo experience low self‐esteem. The disease negatively affects quality of life . Vitiligo has a complex pathogenesis, and the precise etiology is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who have vitiligo experience low self‐esteem. The disease negatively affects quality of life . Vitiligo has a complex pathogenesis, and the precise etiology is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The disease negatively affects quality of life. [1][2][3] Vitiligo has a complex pathogenesis, and the precise etiology is still unclear. It was suggested that different factors especially genetic influences, stress, autoimmune predisposition, dysfunctional biochemical pathway, and trauma may act synergistically in disappearance of melanocytes from the skin.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common depigmentation disorder, affecting approximately 0.5–2.0% of the population, with no sex or race predilection (Ezzedine, Eleftheriadou, Whitton, & van Geel, ). Several theories have been suggested to explain the pathogenesis of vitiligo and the mechanisms finally leading to the loss of functional melanocytes from the epidermis (Bishnoi & Parsad, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to loss of melanocytes in individuals affected by vitiligo, one can also expect an increased incidence of non-melanoma cancer and actinic keratose (Zhang et al, 2016). Arresting the progression of lesions and repigmentation of formed lesions remains to be a crucial strategy for treatment (Bishnoi & Parsad, 2018). AK-STAT inhibitors have demonstrated promising outcomes in the treatment of vitiligo, including repigmentation in topical applications.…”
Section: Introductionmentioning
confidence: 99%